The role of pair-rule genes in Tribolium segmentation - Choe, Chong Pyo (Kansas State University, 2006)
All arthropods share a segmented body plan. Detailed studies on segmentation mechanisms in the long-germ insect Drosophila melanogaster identified a segmentation hierarchy composed of maternal, gap, pair-rule, and segment polarity genes. In this hierarchy, pair-rule genes play an important role to translate gradients of regional information from maternal and gap genes into segmental expression of segment polarity genes. However, our understanding of the role of pair-rule genes in other short-germ insects and basally branching arthropods is still limited. To gain insights into the role of pair-rule genes in short-germ segmentation, I analyzed genetic interactions as well as expression patterns and functions of homologs of Drosophila pair-rule genes in the short-germ insect Tribolium castaneum. Interestingly, despite the pair-rule like expression patterns of Tribolium homologs of almost all eight canonical Drosophila pair-rule genes, only five have a segmentation function. Knock-down of primary pair-rule genes caused asegmental and truncated phenotypes while knock-down of secondary pair-rule genes caused typical pair-rule phenotypes. Epistatic analysis between the genes revealed that primary pair-rule genes form a gene circuit to prepattern a two-segmental unit, and secondary pair-rule genes are downstream targets of the gene circuit. The typical pair-rule phenotypes observed in secondary pair-rule gene RNAi embryos led to a detailed comparative analysis of the role of paired (prd) and sloppy-paired (slp) between Drosophila and Tribolium. This study revealed that prd is functionally conserved while the functional parasegmental register for Tribolium slp is opposite that of Drosophila slp. The fact that the register of slp function has evolved differently in the lineages leading to Drosophila and Tribolium reveals an unprecedented flexibility in pair-rule patterning. Despite this flexibility in pair-rule patterning between Drosophila and Tribolium, segmental expression of engrailed (en) and wingless (wg) at parasegmental boundaries is conserved in both insects. Analysis of double and triple RNAi for pair-rule genes in Tribolium revealed that the primary pair-rule genes even-skipped and runt are redeployed to directly regulate en and wg with prd or slp at parasegmental boundaries. This redeployment of primary pair-rule genes seem to compensate for the apparently fewer number of functional secondary pair-rule genes in Tribolium segmentation.
Keywords: Insect segmentation; Tribolium castaneum; Pair-rule genes; Developmental Biology; Short-germ; Evolution; Biology, Genetics (0369); Biology, Molecular (0307)